2008
DOI: 10.1016/j.cellbi.2008.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drug induced developmental toxicity using human embryonic stem cells

Abstract: Embryonic stem (ES) cells are unique as they have the potential to be generated in large numbers and the ability to differentiate into the three germ layers via embryoid body (EB) formation. This property could be utilized as an index to study initial mammalian development. We have investigated the utility of a comprehensively characterized human ES (hES) cell line (ReliCellhES1) for testing the embryotoxic effects of compounds using cytotoxicity assays. Further, we performed real time gene expression analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 33 publications
4
37
2
Order By: Relevance
“…For instance, it was shown that while retinoic acid (RA) and 13-cis RA (13RA) exerted cytotoxic effects on hESCs, only the former compound induced cytotoxicity in mESCs despite both compounds being well-known agents of embryotoxicity 94 . However, testing for cytotoxicity is not a sufficient end-point to establish reproductive toxicity and hence incorporation of biomarkers to monitor changes in early lineage transcripts and cardiac development has been proposed 91,95 . In comparison to animal models, hPSCs have proven their effectiveness as an embryotoxic test system 96 .…”
Section: Human Pscs and Embryotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, it was shown that while retinoic acid (RA) and 13-cis RA (13RA) exerted cytotoxic effects on hESCs, only the former compound induced cytotoxicity in mESCs despite both compounds being well-known agents of embryotoxicity 94 . However, testing for cytotoxicity is not a sufficient end-point to establish reproductive toxicity and hence incorporation of biomarkers to monitor changes in early lineage transcripts and cardiac development has been proposed 91,95 . In comparison to animal models, hPSCs have proven their effectiveness as an embryotoxic test system 96 .…”
Section: Human Pscs and Embryotoxicitymentioning
confidence: 99%
“…In an attempt to address species variation, hPSCs have been proposed as suitable models for investigating embryotoxicity 91,93,94 . For instance, it was shown that while retinoic acid (RA) and 13-cis RA (13RA) exerted cytotoxic effects on hESCs, only the former compound induced cytotoxicity in mESCs despite both compounds being well-known agents of embryotoxicity 94 .…”
Section: Human Pscs and Embryotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…A second interesting study has evaluated the potential of hESC to provide information on toxic chemicals using two non-embryotoxic, two weakly embryotoxic, and two strongly embryotoxic chemicals [46]. Cytotoxic indices were determined using cells representing the embryo (hESC), fetus (human embryoid bodies) and adults (human foreskin fibroblasts).…”
Section: Examples Of Studies That Have Been Donementioning
confidence: 99%
“…The authors concluded that although this initial assay showed promise, additional research would be needed to standardize a human EST. Mehta et al [2008] attempted to increase the predictivity of the test by examining gene expression of each of the three germ layers as the endpoint of differentiation in a single hESC line. The authors concluded that the "implementation of the EST in regulatory test guidelines would demonstrate the importance of in vitro assays as valuable components of the risk/hazard assessment process" [Mehta et al 2008].…”
Section: Mouse Embryonic Stem Cell Test (Mest)mentioning
confidence: 99%